**Answer:**

d

**Step-by-step explanation:**

**Answer:**

jordan drinks 4.5 cup of water

**Answer:**

-8y +8v +24

**Step-by-step explanation:**

-8(y-v-3)

Multiply each term inside the parentheses by -8

-8y -v*-8 -3*-8

-8y +8v +24

- 2 1/4 * 3 1/3

= -9/4 * 10/3

= -90/12

= = -7 1/2 answer

**Answer:**

Y' (3, 3 ) , Z' (2, - 1 )

**Step-by-step explanation:**

Given

X (3, - 1 ) → X' (6, 1 )

This represents + 3 in the x- direction and + 2 in the y- direction

Then the translation rule is

(x, y ) → (x + 3, y + 2 ) , then

Y (0, 1 ) → Y' (0 + 3, 1 + 2 ) → Y' (3, 3 )

Z (- 1, - 3 ) → Z' (- 1 + 3, - 3 + 2 ) → Z' (2, - 1 )